When the world collapses : changed worldview and social reconstruction in a traumatized community - Čorkalo Biruški, Dinka (Array, 2014)
Background: Traumatic experience can affect the individual’s basic beliefs about the world as a predictable and safe place. One of the cornerstones in recovery from trauma is reestablishment of safety, connectedness, and the shattered schema of a worldview. Objective: This study explored the role of negatively changed worldview in the relationship between war-related traumatization and readiness for social reconstruction of intergroup relations in a post-conflict community measured by three processes: intergroup rapprochement, rebuilding trust, and need for apology. It was hypothesized that more traumatized people are less supportive of social reconstruction and that this relationship is mediated by the changed worldview. Method: The study included a community random sample of 333 adults in the city of Vukovar, Croatia, that was most devastated during the 1991–1995 war. Six instruments were administered: Stressful Events Scale, Impact of Event Scale-Revised, Changed Worldview Scale, and three scales measuring the post-conflict social reconstruction processes: Intergroup Rapprochement, Intergroup Trust and Need for Apology. Results: Mediation analyses showed that the worldview change fully mediated between traumatization and all three aspects of social reconstruction. Conclusions: In a population exposed to war traumatization the worldview change mediates post-conflict social recovery of community relations.